Grid Mapping the Northern Plains of Mars: A New Overview of Recent Water‐ and Ice‐Related Landforms in Acidalia Planitia. Issue 2 (21st February 2019) - Orgel, Csilla; Hauber, Ernst; van Gasselt, Stephan; Reiss, Dennis; Johnsson, Andreas; Ramsdale, Jason D.; Smith, Isaac; Swirad, Zuzanna M.; Séjourné, Antoine; Wilson, Jack T.; Balme, Matthew R.; Conway, Susan J.; et al.
Abstract: We used a grid‐mapping technique to analyze the distribution of 13 water‐ and ice‐related landforms in Acidalia Planitia as part of a joint effort to study the three main basins in the northern lowlands of Mars, that is, Acidalia, Utopia, and Arcadia Planitiae. The landforms were mapped at full Context Camera resolution along a 300‐km‐wide strip from 20°N to 84°N. We identified four landform assemblages: (1) Geologically recent polar cap (massive ice), which superposes the latitude‐dependent mantle (LDM) (LA1); (2) ice‐related landforms, such as LDM, textured terrain, small‐scale polygons, scalloped terrain, large‐scale viscous flow features, and gullies, which have an overlapping distribution (LA2); (3) surface features possibly related to water and subsurface sediment mobilization (LA3; kilometer‐scale polygons, large pitted mounds, small pitted mounds, thumbprint terrain); and (4) irregularly shaped pits with raised rims on equator‐facing slopes. Pits are likely the result of an energetic release of volatiles (H2 O, CO2, and CH4 ), rather than impact‐, volcanism‐, or wind‐related processes. LDM occurs ubiquitously from 44°N to 78°N in Acidalia Planitia. Various observations suggest an origin of air fall deposition of LDM, which contains less ice in the uppermost tens of meters in Acidalia Planitia than in Arcadia and Utopia Planitiae. However, LDM may be thicker and more extended in the past in Acidalia Planitia. The transition between LDM‐free terrain and LDM is situated further north than in Utopia and Arcadia Planitiae, suggesting different past and/or present climatic conditions among the main basins in the northern lowlands. Plain Language Summary: We studied water and ice‐related landforms in the Acidalia Planitia, Mars. We used a new approach, a grid system of 20 × 20‐km cells, along a 300‐km‐wide strip (east‐west) from latitude 20°N to 84°N (south‐north). This work is a joint effort to study three major basins in the northern plains: Acidalia, Utopia, and Arcadia Planitiae. We conducted a regional mapping of specific landforms at 6 m/pixel resolution data and compared the results to different data products, such as geological maps, topography, radar, and climatic models. We proved that latitude‐dependent mantle occurs from 44°N to 78°N in Acidalia Planitia and has an air fall origin related to past climatic cycles. These deposits are composed of mixture of fine‐grained ice and dust. The distribution of this landform extends further south in Utopia and Arcadia Planitae suggesting different past/present climatic conditions in the northern lowlands. Key Points: A grid‐mapping approach is demonstrated to be an effective technique to map small‐scale landforms in Acidalia Planitia LDM begins to occur north of 44 degree N in Acidalia Planitia, a transition that is at a higher latitude than in Utopia and Arcadia Planitiae Irregular‐shaped pits on equator‐facing scarps suggest an energetic release of volatiles (H2 O, CO2, CH4 )